First Annual Report of Severn Wildfowl Trust: 1948 - Anonymous, Anonymous (Wildfowl, 1948)
No abstract available. Contents include the following: Map of New Grounds, First Annual General Meeting–Report of Council, 1947, Balance Sheet, The Appeal for Funds, Acknowledgements, BIRD REPORT: The Wild Geese, The Rocket Net, Notable Records of Other Birds, The Decoy, The Waterfowl Collection, List of Members.